Impact of high‐intensity interval training with or without l‐citrulline on physical performance, skeletal muscle, and adipose tissue in obese older adults. Issue 3 (7th March 2022) - Marcangeli, Vincent; Youssef, Layale; Dulac, Maude; Carvalho, Livia P.; Hajj‐Boutros, Guy; Reynaud, Olivier; Guegan, Bénédicte; Buckinx, Fanny; Gaudreau, Pierrette; Morais, José A.; Mauriège, Pascale; Noirez, Philippe; et al.
Abstract: Background: Aging is associated with a progressive decline in skeletal muscle mass and strength as well as an increase in adiposity. These changes may have devastating impact on the quality of life of older adults. Mitochondrial dysfunctions have been implicated in aging‐related and obesity‐related deterioration of muscle function. Impairments in mitochondrial quality control processes (biogenesis, fusion, fission, and mitophagy) may underlie this accumulation of mitochondrial dysfunction. High‐intensity interval training (HIIT) was shown to improve muscle and mitochondrial function in healthy young and old adults and to improve body composition in obese older adults. Recent studies also positioned citrulline (CIT) supplementation as a promising intervention to counter obesity‐related and aging‐related muscle dysfunction. In the present study, our objectives were to assess whether HIIT, alone or with CIT, improves muscle function, functional capacities, adipose tissue gene expression, and mitochondrial quality control processes in obese older adults. Methods: Eighty‐one‐old and obese participants underwent a 12 week HIIT with or without CIT on an elliptical trainer [HIIT‐CIT: 20 men/25 women, 67.2 ± 5.0 years; HIIT‐placebo (PLA): 18 men/18 women, 68.1 ± 4.1 years]. Handgrip and quadriceps strength, lower limb muscle power, body composition, waist circumference, and functional capacities were assessed pre and post intervention. Vastus lateralis muscle biopsies were performed in a subset of participants to quantify markers of mitochondrial content (TOM20 and OXPHOS subunits), biogenesis (TFAM), fusion (MFN1&2, OPA1), fission (DRP1), and mitophagy (Parkin). Subcutaneous abdominal adipose tissue biopsies were also performed to assess the expression of genes involved in lipid metabolism. Results: HIIT‐PLA and HIIT‐CIT displayed improvements in functional capacities ( P < 0.05), total (mean ± SD: HIIT‐PLA: +1.27 ± 3.19%, HIIT‐CIT: +1.05 ± 2.91%, P < 0.05) and leg lean mass (HIIT‐PLA: +1.62 ± 3.85%, HIIT‐CIT: +1.28 ± 4.82%, P < 0.05), waist circumference (HIIT‐PLA: −2.2 ± 2.9 cm, HIIT‐CIT: −2.6 ± 2.5 cm, P < 0.05), and muscle power (HIIT‐PLA: +15.81 ± 18.02%, HIIT‐CIT: +14.62 ± 20.02%, P < 0.05). Only HIIT‐CIT decreased fat mass (−1.04 ± 2.42%, P < 0.05) and increased handgrip and quadriceps strength (+4.28 ± 9.36% and +10.32 ± 14.38%, respectively, P < 0.05). Both groups increased markers of muscle mitochondrial content, mitochondrial fusion, and mitophagy ( P < 0.05). Only HIIT‐CIT decreased the expression of the lipid droplet‐associated protein CIDEA ( P < 0.001). Conclusions: High‐intensity interval training is effective in improving functional capacities, lean mass, muscle power, and waist circumference in obese older adults. HIIT also increases markers of mitochondrial biogenesis, mitochondrial fusion, and mitophagy. Importantly, adding CIT to HIIT results in a greater increase in muscle strength and a significant decrease in fat mass. The present study therefore positions HIIT combined with CIT as an effective intervention to improve the health status of obese older adults.